2009
DOI: 10.1002/pmic.200800840
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rice plant resistance to the Brown Planthopper (Nilaparvata lugens): A proteomic approach

Abstract: Engineering and breeding resistant plant varieties are the most effective and environmentally friendly ways to control agricultural pests and improve crop performance. However, the mechanism of plant resistance to pests is poorly understood. Here we used a quantitative mass-spectrometry-based proteomic approach for comparative analysis of expression profiles of proteins in rice leaf sheaths in responses to infestation by the brown planthopper (Nilaparvata lugens Stål, BPH), which is a serious rice crop pest. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 48 publications
8
106
1
4
Order By: Relevance
“…A comprehensive analysis of the transcriptome response in Nicotiana attenuata, a wild relative of tobacco, identified several gene families as being activated in response to insect-inflicted damage, including several transcriptional regulators and protein kinases (Gilardoni et al, 2010; Hermsmeier et al, 2001). Similar results were observed in other plant species (Reymond et al, 2004;Wei et al, 2009). Plant responses to defoliators have been broadly characterized in a number of different plant species (e.g.…”
Section: Introductionsupporting
confidence: 82%
“…A comprehensive analysis of the transcriptome response in Nicotiana attenuata, a wild relative of tobacco, identified several gene families as being activated in response to insect-inflicted damage, including several transcriptional regulators and protein kinases (Gilardoni et al, 2010; Hermsmeier et al, 2001). Similar results were observed in other plant species (Reymond et al, 2004;Wei et al, 2009). Plant responses to defoliators have been broadly characterized in a number of different plant species (e.g.…”
Section: Introductionsupporting
confidence: 82%
“…10 Recent findings in, proteomic analysis of rice have demonstrated that several ribosomal proteins are upregulated after a Nilaparvata lugens infection. 11 Interestingly, the L10 ribosomal protein is upregulated in nrt2 after P. syringae infection compared with Ws. This protein has been shown to be a component in the nuclear shuttle protein-interacting kinase of Arabidopsis, that participates in METLIN (metlin.scripps.edu/).…”
Section: Pre-existing Metabolic Changes In Nrt2 Mutant May Contributementioning
confidence: 96%
“…In most cases, the latter hypothesis, reduced photosynthesis in response to herbivory, is supported by actual measurements of changes in photosynthesis rate, photosynthesis-related gene expression, or production of proteins that are part of the photosynthetic apparatus (Reymond et al, 2004;Giri et al, 2006;Wei et al, 2009;Bilgin et al, 2010;Coppola et al, 2013;Appel et al, 2014). Reduced photosynthetic capacity can exceed what would be expected from the observed amount of foliar tissue that is removed (Zangerl et al, 2002).…”
Section: Carbohydrate Metabolismmentioning
confidence: 97%